1942
DOI: 10.1128/jb.43.3.347-363.1942
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium kluyverii, an Organism Concerned in the Formation of Caproic Acid from Ethyl Alcohol

Abstract: When ethyl alcohol is acted upon by the methane-producing organism, Methanobacterium omelianskii, acetic acid is the sole oxidation product (Barker (1939-40, 1941)). But with alcoholcontaining enrichment cultures for the same organism it often happens that acetic acid is formed in only relatively small amounts, while most of the alcohol is converted into caproic and butyric acids (Barker (1937)). In some cultures as much as 75 per cent by weight of the volatile acid is caproic. Microscopic examination has show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
62
0

Year Published

1950
1950
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 6 publications
0
62
0
Order By: Relevance
“…Tissierella produces acetic, butyric, isovaleric acids (Vos et al, 2009). C. kluyveri produces caproic acid (Barker and Taha, 1942;Weimer and Stevenson, 2012) Streptococcus in new pit muds were higher than these in aged pit muds. The reduction of these three genera resulted in the reduction of lactic acid and ethyl lactate in aged pit muds.…”
Section: Discussionmentioning
confidence: 97%
“…Tissierella produces acetic, butyric, isovaleric acids (Vos et al, 2009). C. kluyveri produces caproic acid (Barker and Taha, 1942;Weimer and Stevenson, 2012) Streptococcus in new pit muds were higher than these in aged pit muds. The reduction of these three genera resulted in the reduction of lactic acid and ethyl lactate in aged pit muds.…”
Section: Discussionmentioning
confidence: 97%
“…This stepwise two-carbon increase of the carboxylic acid acyl-chain is why this metabolism is often named chain elongation. Clostridium kluyveri was the first isolated bacterium capable of producing caproic acid and since then it has been thoroughly investigated, mostly focusing on its unique metabolism [10][11][12][13] .In what concerns the engineering of caproic acid bio-production, most studies have used open communities because they can offer several advantages over axenic cultures: (i) no need for sterility, as the community is functionally stabilized by the operational conditions; (ii) increased process stability under changing conditions, i.e. present but inactive species can take over the role of failing organisms, so-called functional redundancy in open ) in the specific case of chain elongation for production of caproic acid, open communities have been shown to outperform the pure culture C. kluyveri 15 .…”
mentioning
confidence: 99%
“…This stepwise two-carbon increase of the carboxylic acid acyl-chain is why this metabolism is often named chain elongation. Clostridium kluyveri was the first isolated bacterium capable of producing caproic acid and since then it has been thoroughly investigated, mostly focusing on its unique metabolism [10][11][12][13] .…”
mentioning
confidence: 99%
“…Copy numbers of C. kluyveri in aged pit mud are reportedly higher than those in new pit mud (Hu et al 2015;Zhang et al 2017a, b), which we also observed. C. kluyveri can produce caproic acid (Barker and Taha 1942;Weimer and Stevenson 2012), which is the precursor for ethyl caproate, the typical flavour compound of Luzhou-flavoured liquor. Some trends in microbial indicators and environmental factors varied in new and aged pit mud.…”
Section: Discussionmentioning
confidence: 99%